Code Switching and Code Mixing in Maxwell Salvador's Oral Speech on YouTube: A Sociolinguistic Study - Faza Nur ‘Ashifa; Abdul Kholiq (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms and functions of code switching and code mixing in the spoken language of Maxwell Salvador Surya Atmaja on his YouTube channel. The method used in this study uses a sociolinguistic approach based on the code switching theory by Appel & Muysken and the code mixing theory by Muysken with a qualitative approach with a descriptive research type. The data collection technique uses a listening, reading, and note-taking technique adapted to Creswell's data collection type, namely documents and audio-visual. The data analysis technique is carried out with stages according to Creswell, namely video transcription, data identification and classification, tabulation and codification, data analysis, and data presentation. The results of the study show that the forms of code switching found are Tag-switching and Intersentential-switching, while the forms of code mixing include Insertion, Alternation, and Congruent Lexicalization. The functions of code switching found are Referential Function, Directioe and Imaginary Function, and Expression Function. While the functions of code mixing include Referential Function, Directioe and Imaginary Function, Expression Function, and Phatic Function. The conclusion of this study shows that the use of code switching and code mixing occurs because the speech used by speakers is more flexible and unstructured so that it can trigger the emergence of language switching or mixing.